Fabrication, optimisation and in vitro evaluation of docetaxel and curcumin Co-loaded nanostructured lipid carriers for improved antitumor activity against non-small cell lung carcinoma. (16th November 2020) - Rawal, Shruti; Patel, Bhoomika; Patel, Mayur M.
Abstract: Aim: To develop docetaxel (DT) and curcumin (CUR) co-loaded nanostructured lipid carriers (DTCR-NLCs) for ratiometric co-targeting to non-small cell lung carcinoma (NSCLC) cells. Methods: The DTCR-NLCs were developed by employing a high-pressure homogenisation technique and optimised by employing a rotatable central composite design response surface methodology (RCCD-RSM) via the design of experiments (DoE) approach. Results: The optimised DTCR-NLCs had a particle size (D90) of 150.2 ± 5.2 nm, Pdi of 0.263 ± 0.15, zeta potential of +26.3 ± 5.2 mv. The % drug loading (% DL) of DT and CUR was observed to be 1.38 ± 0.98 and 2.99 ± 1.24, respectively. Dissolution studies depicted a pH-independent drug release (≈98% drug release at 144 h). The DTCR-NLCs were stable and haemocompatible. MTT cell viability assay of DTCR-NLCs demonstrated considerably increased cytotoxicity towards NCI-H460 cells. Conclusions: The developed DTCR-NLCs heralds the future of an efficacious and safer Taxane therapy for NSCLC.